Case Report: Ectopic pulmonary embolism as a complication of bronchial artery embolization - Liu, Min; Liu, Jixiang; Chen, Shen; Gao, Xiaoyan; Zhong, Jinnan; Sun, Lu; Li, Fajiu; Li, Chenghong (Frontiers in Cardiovascular Medicine, 2024)
Bronchial artery embolization (BAE) is currently the first-line treatment for massive hemoptysis. Previous studies have proven its safety and efficacy, with mild, transient, and reversible complications. This case described a patient with congenital multiple bronchopulmonary fistulas who underwent BAE due to massive hemoptysis. However, due to overlooked and misdiagnosed a atypical fistula, the patient experienced ectopic pulmonary embolism and subsequently secondary pulmonary infarction. He eventually exhibited a full postoperative recovery following percutaneous catheter-directed embolectomy. This case revealed a type of occult fistula masked by multiple bronchial artery branches, which may be a potential risk factor for ectopic pulmonary embolism during BAE. We propose that it is crucial to identify abnormal anastomosis especially atypical fistula and select appropriate embolization materials during BAE.